The Effect of Job Stress, Compensation and Job Satisfaction on Turnover Intention through Organizational Commitment as an Intervening Variable for Employees: Pengaruh Stress Kerja, Kompensasi dan Kepuasan Kerja Terhadap Turnover Intention Melalui Komitmen Organisasi Sebagai Variabel Intervening Pada Karyawan - Arum Tri Wahyuni; Misti Hariasih (Academia Open, 2021)
This study aims to examine the effect of work stress, compensation and job satisfaction on turnover intention through organizational commitment as an intervening variable. This study uses the approach used in this study is a quantitative approach. The population in this study were 100 employees. The sampling technique used the total sampling technique method (saturated sample). The sample in this study were 100 employees at PT. Jico Agung Sidoarjo. The data used in this study are questionnaire data and data sourced from PT. Jico Agung Sidoarjo. Data collection techniques using questionnaires and observation. Data analysis using smartPLS 3.2.8 Software. The results obtained from this path analysis are obtained from the results that work stress has no significant effect on turnover intention, compensation has a significant effect on turnover intention, job satisfaction has a significant effect on turnover intention, work stress has a significant effect on organizational commitment, compensation has a significant effect on organizational commitment. , job satisfaction has a significant effect on organizational commitment, organizational commitment has a significant effect on turnover intention, job stress has a significant effect on turnover intention through organizational commitment as an intervening variable, compensation has a significant effect on turnover intention through organizational commitment as an intervening variable, job satisfaction has a significant effect on turnover intention through organizational commitment as an intervening variable.